Cysteine restriction‐specific effects of sulfur amino acid restriction on lipid metabolism. Issue 12 (19th November 2022) - Nichenametla, Sailendra N.; Mattocks, Dwight A. L.; Cooke, Diana; Midya, Vishal; Malloy, Virginia L.; Mansilla, Wilfredo; Øvrebø, Bente; Turner, Cheryl; Bastani, Nasser E.; Sokolová, Jitka; Pavlíková, Markéta; Richie, John P.; et al.
Abstract: Decreasing the dietary intake of methionine exerts robust anti‐adiposity effects in rodents but modest effects in humans. Since cysteine can be synthesized from methionine, animal diets are formulated by decreasing methionine and eliminating cysteine. Such diets exert both methionine restriction (MR) and cysteine restriction (CR), that is, sulfur amino acid restriction (SAAR). Contrarily, SAAR diets formulated for human consumption included cysteine, and thus might have exerted only MR. Epidemiological studies positively correlate body adiposity with plasma cysteine but not methionine, suggesting that CR, but not MR, is responsible for the anti‐adiposity effects of SAAR. Whether this is true, and, if so, the underlying mechanisms are unknown. Using methionine‐ and cysteine‐titrated diets, we demonstrate that the anti‐adiposity effects of SAAR are due to CR. Data indicate that CR increases serinogenesis (serine biosynthesis from non‐glucose substrates) by diverting substrates from glyceroneogenesis, which is essential for fatty acid reesterification and triglyceride synthesis. Molecular data suggest that CR depletes hepatic glutathione and induces Nrf2 and its downstream targets Phgdh (the serine biosynthetic enzyme) and Pepck‐M. In mice, the magnitude of SAAR‐induced changes in molecular markers depended on dietary fat concentration (60% fat >10% fat), sex (males > females), and age‐at‐onset (young > adult). Our findings are translationally relevant as we found negative and positive correlations of plasma serine and cysteine, respectively, with triglycerides and metabolic syndrome criteria in a cross‐sectional epidemiological study. Controlled feeding of low‐SAA, high‐polyunsaturated fatty acid diets increased plasma serine in humans. Serinogenesis might be a target for treating hypertriglyceridemia. Abstract : The proposed mechanism of CR‐specific effects of SAAR on adipose metabolism. (1) Due to the lack of Cys in SAAR diets, it imposes both MR and CR. CR specifically results in decreased biosynthesis of the tripeptide glutathione. (2) Lower hepatic glutathione increases the abundance of the transcription factor Nrf2, which translocates to the nucleus and induces the transcription of Phgdh. (3) Increase in the transcription and translation of Phgdh and Pck‐2 results in higher hepatic serinogenesis (Ser biosynthesis from substrates other than glucose, that is, from oxaloacetic acid). (4) Higher serinogenesis competes with glyceroneogenesis as both pathways use the same set of substrates, which results in lower fatty acid re‐esterification. Note : broken arrows represent the presence of other biochemical intermediates not shown in the figure. Up and down arrows adjacent to the metabolic intermediates represent an increase and decrease, respectively. 3PG, 3‐phosphoglycerate; OAA, oxaloacetic acid; DHAP, dihydroxyacetone phosphate; PEP, phosphoenolpyruvate; FA, fatty acids.